The Commonwealth of the Independent States as an Organization of Missed Opportunities: the Russian Leadership's Errors in the 1990s - V. G. Burkov; K. E. Mescheryakov; R. G. Shamgunov (Евразийская интеграция: экономика, право, политика, 2019)
Following the collapse of the USSR, the post-Soviet states applied their foreign policy and solved economic and military problems in cooperation with one another. They established the Commonwealth of the Independent States and the other integration associations, both within and beyond the CIS. This article deals with the problems of integration of the post-Soviet states. It discovers the main reasons why the CIS failed to grow in a very integration union. The authors believe that the main cause was a short-foresighted policy of the Russian leadership under the presidency of Boris Yeltsin